Introduction to the Special Issue - The ethical, aesthetic, and political dimensions of research in/of/with daily life: a tribute to public schools! (Práxis Educativa, 2024)
Introduction to the Special Issue - The ethical, aesthetic, and political dimensions of research in/of/with daily life: a tribute to public schools!